1999
DOI: 10.1016/s0736-5748(99)00052-0
|View full text |Cite
|
Sign up to set email alerts
|

Cells encapsulated in alginate: a potential system for delivery of recombinant proteins to malignant brain tumours

Abstract: Growth and progression of malignant brain tumours occurs in a micromilieu consisting of both tumour and normal cells. Several proteins have been identified with the potential of interfering directly with tumour cells or with the neovascularisation process, thereby inhibiting tumour growth. A continuous delivery of such inhibitory proteins to the tumour microenvironment by genetically engineered cells could theoretically be of considerable therapeutic importance. In this study we have investigated the growth ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
47
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 22 publications
4
47
0
Order By: Relevance
“…A number of studies have used alginate, derived from brown seaweed, as a means of encapsulating cells for in vivo implantation, thereby isolating them from the host immune cells. Previous studies demonstrated the coating has no effect on cellular growth or proliferation, and indicated that in the first week after implantation in vivo, mononuclear cells migrated to the rim of the alginate spheroid but there was no penetration, and over the following nine weeks, the number of migrating cells gradually decreased (Read et al, 1999(Read et al, , 2001. The permeability to diffusible molecules was demonstrated by Hoescht staining of tumour cells, following addition to the culture medium, and the release of VEGF but not cells into the well suggesting that coating allowed the passage of molecules but not cells into and out of the spheroids.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A number of studies have used alginate, derived from brown seaweed, as a means of encapsulating cells for in vivo implantation, thereby isolating them from the host immune cells. Previous studies demonstrated the coating has no effect on cellular growth or proliferation, and indicated that in the first week after implantation in vivo, mononuclear cells migrated to the rim of the alginate spheroid but there was no penetration, and over the following nine weeks, the number of migrating cells gradually decreased (Read et al, 1999(Read et al, , 2001. The permeability to diffusible molecules was demonstrated by Hoescht staining of tumour cells, following addition to the culture medium, and the release of VEGF but not cells into the well suggesting that coating allowed the passage of molecules but not cells into and out of the spheroids.…”
Section: Discussionmentioning
confidence: 99%
“…At the end of each experiment all tissue from the chamber was processed and stained, and demonstrated that the tumour cells remained viable, that macrophages remained within the spheroid throughout the experimental period and that host macrophages had not permeated the alginate coating. The size of each spheroid was not measured at the end of the experiments, but previous studies have shown that it is possible for cell growth to occur within the confines of the agarose coating (Read et al, 1999(Read et al, , 2001). …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…32 Briefly, HSPG-bFGF exposed to heparanase in presence or absence of suramin analogues was mixed with alginate gel (1.8%). The mixture was used to prepare beads, at a volume of 10 ml, by dropping them into a hardening solution of 1.5% CaCl 2 .…”
Section: Encapsulation Of Bfgf-hspg In Alginate Microspheres and In Vmentioning
confidence: 99%